Carbene‐Catalyzed Activation of C−Si Bonds for Chemo‐ and Enantioselective Cross Brook–Benzoin Reaction. Issue 34 (8th July 2022) - Tang, Chenghao; Wang, Wei; Luo, Guoyong; Song, Chaoyang; Bao, Zhaowei; Li, Pei; Hao, Gefei; Chi, Yonggui Robin; Jin, Zhichao
Abstract: The first carbene‐catalyzed asymmetric chemoselective cross silyl benzoin (Brook–Benzoin) reaction has been developed. Key steps of this reaction involve activation of the carbon–silicon bond of an acylsilane by a chiral N‐heterocyclic carbene (NHC) catalyst to form a silyl acyl anion intermediate. These acyl anions then undergo an addition reaction with indole aldehydes in a highly chemo‐ and enantioselective manner to afford α‐silyloxy ketones with excellent optical purities. The reaction mechanism of this cross Brook–Benzoin reaction was investigated through both experimental and computational methods. The chiral α‐hydroxy ketone derivatives obtained by this approach show promising, agrochemically interesting activity against harmful plant bacteria. Abstract : The first N‐heterocyclic carbene (NHC) catalyzed chemo‐ and enantioselective Brook–Benzoin reaction is disclosed. This reaction proceeds via silyl acyl anion intermediates and enables the synthesis of α‐silyloxy ketones bearing a wide range of functional groups in good to excellent yields and enantioselectivities.